2012
DOI: 10.5222/ankem.2012.001
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Isolated from Various Clinical Samples and their Antibiotic Susceptibilities in Intensive Care Unit Patients

Abstract: Microorganisms Isolated from Various Clinical Samples and their Antibiotic Susceptibilities in Intensive Care Unit Patients It is extremely important to identify the predominant infecting organisms and antibiotic resistance profiles in hospitals primarily departments at risk for infection such as intensive care units in terms of rational use of antibiotics and hospital infection control measures. In this study, it was aimed to determine the antibiotic resistance rates of microorganisms isolated from various cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In a study by El-Kersh et al [17] , HLGR and HLSR were detected in enterococci at rates of 25% and 11%, respectively. In a study by Ertürk et al [18] , these rates were found to be 25% and 50%, respectively. In yet another study, 67.9% of enterococci showed HLGR and 67.9% showed HLSR [19] .…”
Section: Discussionmentioning
confidence: 90%
“…In a study by El-Kersh et al [17] , HLGR and HLSR were detected in enterococci at rates of 25% and 11%, respectively. In a study by Ertürk et al [18] , these rates were found to be 25% and 50%, respectively. In yet another study, 67.9% of enterococci showed HLGR and 67.9% showed HLSR [19] .…”
Section: Discussionmentioning
confidence: 90%
“…19% E.coli, 16% Acinetobacter spp., 14% Klebsiella spp., and 12% other Gram-negative rods (Citrobacter spp., Enterobacter spp., Proteus spp., and Serratia spp.) have been reported (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies, Gram-negative bacteria have been reported as the most common isolates in VAP patients. Among these, the most common bacteria are Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) . In our study, the microorganisms caused VAP were similar to those studies regarding their order of frequency (Figure 1).…”
Section: Discussionmentioning
confidence: 99%